Soilscapes from Byers Peninsula, Maritime Antarctic: landform-lithology controls in soil formation - JÔNATAS PEDRO DA SILVA; MÁRCIO R. FRANCELINO; ANDRÉ LUIZ L. DE FARIA; HEITOR P. PALMA; ISABELLE DE A. OLIVEIRA; JOSÉ JOÃO L.L. DE SOUZA; CARLOS ERNESTO G.R. SCHAEFER (Anais da Academia Brasileira de Ciências)
Abstract The Byers Peninsula, the largest ice-free area in Maritime Antarctica, is vital for studying landscape-scale natural processes due to its diverse periglacial landforms. This study aim to characterize the soils and environments of its southern sector, focusing on soil-landform-lithology interactions. Thirty-seven soil profiles were classified, collected, and chemically and physically analyzed. Principal component analysis explored relationships among variables in these profiles and 36 others from the Peninsula project database. The soils are generally shallow, with lithic or paralithic contact within the first meter. Four main soil groups were identified: patterned-ground soils on plateaus, ornithogenic soils, non-ornithogenic soils, and non-ornithogenic sodic and sandy soils on beaches and marine terraces. The Peninsula, divided into six geological units, represents a diverse periglacial morphogenetic system. Sixteen landform types were identified, each associated with different processes, topographies, lithologies, altitudes, and orientations, highlighting the importance of periglacial morphogenesis. Stable soilscapes, such as upper cryoplanation platforms, raised beaches, volcanic plugs, and ornithogenically influenced areas, show greater soil development and weathering. In contrast, dynamic periglacial landforms like scree stony slopes and talus exhibit minimal soil development and instability. The Byers Peninsula’s pedodiversity is due to its varied lithologies, landforms, extensive ornithogenic influences from seabirds, and long-term vegetation establishment.